Macromolecular nanoparticles to attenuate both reactive oxygen species and inflammatory damage for treating Alzheimer's disease - Bosong Zhang; Yufang Zhao; Kai Guo; Hui Tian; Cao Wang; Ruiqi Wang; Yue Chen; Xiongbiao Chen; Hongxia Zheng; Bingxin Gao; Jieyi Shen; Weiming Tian (Wiley, 2023)
Abstract Prevention and early intervention are the current focus of treatment for Alzheimer's disease (AD). An increase in reactive oxygen species (ROS) is a feature of the early stages of AD, thus suggesting that the removal of excess ROS can be a viable method of improving AD. Natural polyphenols are able to scavenge ROS and thus promising for treating AD. However, some issues need to be addressed. Among them, important are that most polyphenols are hydrophobic, have low bioavailability in the body, are easily degraded, and that single polyphenols have insufficient antioxidant capacity. In this study, we employed two polyphenols, resveratrol (RES) and oligomeric proanthocyanidin (OPC), and creatively grafted them with hyaluronic acid (HA) to form nanoparticles to address the aforementioned issues. Meanwhile, we strategically grafted the nanoparticles with the B6 peptide, enabling the nanoparticles to cross the blood-brain barrier (BBB) and enter the brain for AD treatment. Our results illustrate that B6‐RES‐OPC‐HA nanoparticles can significantly scavenge ROS, reduce brain inflammation, and improve learning and memory ability in AD mice. B6‐RES‐OPC‐HA nanoparticles have the potential to prevent and alleviate early AD.